URGENCY OF RUNNING HANDLING IN DIVORCE CASE (Study of the Circuit Court Program at the Jantho Syar'iyyah Court) - Misran Misran; Mirza Hazaki (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2020)
According to a 2007 study, the poor face major financial barriers to accessing the Religious Courts relating to court fees and transportation costs to come to court. The Supreme Court responded to these findings by paying great attention to the holding of circuit courts and waiving court fees with the Prodeo process. This response is manifested in the Supreme Court Circular (SEMA) Number 10 of 2010 concerning Guidelines for Legal Aid, which is divided into two attachments, namely attachment A for the General Courts and Annex B for the Religious Courts. Based on data from the Syar'iyah Jantho Court, the divorce case that occurred in Aceh Besar District was classified as high. The divorce rate is the number registered with the Jantho Syar'iyah Court, not including those who are not registered or divorce in secret without being registered with the Jantho Syar'iyah Court. Because traditionally, many people divorce without registering with the Syar'iyah Court, especially those whose social, educational and economic status is middle to lower, coupled with the long distance between their homes and the Syar'iyah Court. Therefore, the problems in this thesis are how the circuit court procedure in divorce cases at the Jantho Syar'iyah Court, how the community's participation in the implementation of circuit courts in divorce cases at the Jantho Syar'iyah Court and how the influence of circuit courts in the social life of the community. With the method of field research (field research) conducted at the Syar'iyah Jantho Court, the result of the research is that the procedure for conducting a circuit court consists of pre-trial stages, namely case registration, appointment of a panel of judges (PMH), appointment of a substitute clerk (PP) and a substitute bailiff. (JSP), Determination of Session Day (PHS), and Summons of the parties. The second stage of the trial is peace efforts, reading of lawsuit / petition, answer-answer, verification, deliberation of the panel of judges, reading of decisions / decisions, implementing the divorce vow and submitting divorce certificates. Insofar as it is implemented, community participation is very high so that it affects public awareness that the termination of a marriage relationship is very important to obtain legal certainty.